Case Study on Tokyo Metropolitan Region, Japan - Research Institute of Urban and Environmental Development (World Bank, Washington, DC, 2019)
Japan entered its period of rapid economic growth in the late 1950s, and for half a century since then, the concentration of population, industries, and other functions in three major metropolitan areas, particularly in Tokyo, was remarkably intense. For the well-balanced development of Greater Tokyo metropolitan area, comprising Tokyo and seven prefectures, the National capital region development plan (NCRDP) was formulated in 1958 under the National region development act 1956. The concept of the plan was to conserve green spaces that embraces the healthy natural environment as well as to carry out the comprehensive development of the Tokyo Metropolis and the surrounding regions as an integrated capital region in order to build a capital region that is suitable for the center of politics, economy and culture. At present, Japan is entering an era of substantial decline and aging of the population decline, which requires to reexamine all plans and policies for reconstructing the society. It is therefore of great importance to reorganize town areas in a compact form, to respond to the problems of uninhabited or abandoned land and dwellings, as well as to strategically manage and renew social capital.